Specifics of the Autobiographical Narrative in “Memoirs” of D. Ovsyaniko-Kulikovskiy - Tatiana Shekhovtsova (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article examines the memoir-autobiographical prose of D. Ovsyaniko-Kulikovskiy as an original example of nonfiction literature. The relevance of the work is due to the active study of the theory and history of memoir-biographical prose in domestic and foreign literary studies, as well as the intensive development of contemporary autobiography. The purpose of the study is to identify the specifics of the autobiographical narrative, the peculiarities of the author's self-identification and the construction of the narrator's life story. It is shown that an autobiographical narrative is constructed as a story for others and a story for oneself. Autobiographical memory contains elements of varying degrees of generalization. While maintaining psychophysical identity, the distance between the autocharacter and the narrator is constantly emphasized.